An analysis of IEEE publications. - Kerbaol, M.
This study reports on a few elements of the scientific production of the IEEE. Other features could be displayed that would be interesting for a better understanding of the trajectories of the societies, journals, etc. The possibility of projecting new data onto the current spaces allows researchers to see if journals are static (the concepts and methods remaining stable) or dynamic (evolutions, ruptures can be tracked). In other words, this type of analysis can be used as a strategic tool to follow the impact and trends in engineering sciences. The fact that the authors concentrate on the IEEE publications prohibits any comparison with other societies publishing engineering papers. Such insights are feasible through the analysis of the INSPEC database. This could bring other clues on the coverage, the competition, and the reaction to new areas.
Keywords: IEEE publications; INSPEC database; Dynamic journals; Engineering papers; Engineering sciences; Scientific production; Static journals